The association of the triglyceride-glucose index and its changes with 5-year all-cause mortality in patients with depression - Cui, Xiao-Jiao; Xie, Bo; Zhou, Yu-Fei; Yi, Xiao-Qing (Frontiers in Psychiatry, 2025)
BackgroundDepression, as the primary contributor to the global disease burden caused by mental disorders, necessitates the urgent discovery of new biomarkers to predict patient prognosis, thereby facilitating early treatment. The triglyceride glucose index (TyG), which has a close relationship with insulin resistance (IR), systemic inflammation, and other factors, could potentially serve as a valuable biomarker for determining depression severity. However, the association of the TyG index and its changes with the long-term prognosis of depression remains unexplored. This article aims to evaluate whether the levels and changes in the TyG index can predict long-term mortality in patients suffering from depression.MethodsA retrospective cohort study was conducted based on the MIMIC-IV (Medical Information Mart in Intensive Care IV) database, involving 1388 patients. Among them, 1120 patients had only one TyG index value during hospitalization, while 266 patients had two or more TyG index values, all of which were included in the analysis. The primary endpoint was 5-year all-cause mortality rate. Restricted cubic spline analysis was also used to evaluate any potential nonlinear correlations. Propensity score matching was performed to reduce any potential baseline bias. Cox proportional hazards analyses were used to adjust for confounders. The Kaplan-Meier method was utilized to compute the cumulative curve.ResultsThe entire cohort exhibited a 5-year all-cause mortality rate of 25.8% (358/1388), with rates of 23.8% (267/1120) and 34% (91/268) in the TyG and TyGVR groups, respectively. According to a multivariate Cox regression model, an increase in TyG elevated the 5-year all-cause mortality risk among depression patients (HR, 1.31; 95% CI, 1.1-1.56; P=0.002). When TyG was treated as a categorical variable, Quartile 4 demonstrated a 61% higher risk of 5-year all-cause mortality in depression patients compared to Quartile 1 (HR, 1.61; 95% CI, 1.15-2.25; P=0.005). Restricted cubic spline analysis revealed a linear relationship between TyG and 5-year all-cause mortality across both the entire and matched cohorts (P values for non-linearity were > 0.05). The Kaplan-Meier curves indicated that patients with elevated TyG experienced significantly higher 5-year all-cause mortality rates in both the entire and matched cohorts (P=0.00041, P=0.035, respectively). A linear association (non-linear P=0.953) was also observed between TyGVR and 5-year all-cause mortality risk. The analysis results across the subgroups were consistent, with no interactions detected (interaction P-values > 0.05).ConclusionsThe TyG index is linked with a 5-year all-cause mortality risk among patients suffering from depression. The dynamic fluctuations in the TyG index could potentially offer more substantial insights in identifying patients at high risk for all-cause mortality.